Production of Lactic Acid from Microalgal Biomass Chlorella vulgar ESP-31 as a feedstock using PVA Immobilized Bacteria L. Plantarum 23 - Nandini , Atika; Nagarajan , Dilirani; Chang , Jo-Shu (Future Science)
Lactic acid is a valuable industrial chemical that is mostly used in the food and non-food industries such as the pharmaceutical industry. Production of lactic acid from renewable materials can be an alternative method to reduce the high production cost associated with raw material acquirement. In this study, polyvinyl alcohol (PVA) immobilized L. plantarum 23 was used. To obtain high lactic acid productivity and yield from renewable feedstock, the optimal fermentation conditions were determined in both batch and continuous mode. The renewable feedstock used was microalgal biomass Chlorella vulgaris ESP-31. The optimal conditions for this fermentation are pH 5.5, temperature 30°C, PVA particle loading 12.5%, PVA concentration 5.25g cell/L, HRT: 2-4 hrs, carbon source concentration 40 g/L. The feedstock was pretreated and hydrolyzed appropriately and the reducing sugars obtained were used. With microalgal sugars as a feedstock in continuous fermentation mode, the maximum lactic acid productivity of 12.59 g/L/h was achieved, compared to glucose (7.39 g/L/h). The highest yield achieved in this study (0,98 g/g) was obtained when using pure glucose as the feedstock. Considering high productivity as the most important parameter, microalgal biomass seems to be the best feedstock for lactic acid production in continuous fermentation, giving high productivity and yield of 12.59 g/L/h and 0.91 g/g, respectively.